Socialist Republic of Vietnam Scaling Up Rural Sanitation : Enabling Environment, Capacity Building System, Evidence Based Learning and Lesson Sharing - World Bank (World Bank, Washington, DC, 2016)
This report concerns two streams of Technical Assistance provided by the World Bank Water and Sanitation Program (WSP) to the Government of Vietnam. They are: strengthening the enabling environment, capacity building systems and evidence-based learning and lesson sharing. Strengthening demand creation and supply chain development together these TAs make up a support program to assist the Government of Vietnam, particularly the Ministry of Health (MOH) in accelerating progress on sanitation under the third National Target Program on Rural Water Supply and Sanitation (NTP3). WSP has supported the government to improve the enabling environment for sanitation service delivery; strengthen rural sanitation supply chains; generate demand for improved sanitation; and inform service delivery models through knowledge and learning. The TAs began in Dec 2012 and are due to end in Jun 2016. This report documents the results and lessons learned from the TA, and makes recommendations for future activities in support of rural sanitation.